Analisis Kandungan Timbal (Pb) Pada Daun Tanaman Teh (Camellia sinensis O.K) dan Tanah Perkebunan Teh yang Berada Di Kawasan Puncak Malino - Azis, Dirgadwijuarti; Jumadi, Oslan; Wiharto, Muhammad (Sainsmat : Jurnal Ilmiah Ilmu Pengetahuan Alam, 2012)
DOWNLOAD PDFDescriptive research was done to know the contents of lead (Pb) in tea leaf (Camellia sinensis) at top, under hills as well as soil of tea plantation at top and under the hills in Malino district. The Variable of these researches was lead content in tea leaf at top and under the hills. Another variable was soial of tea plantation at the top and under hills. The samples were taken from six stations, which were 1, 2, and 3 stations at top hill and 4, 5 and 6 stations at under hill. The leaf sample that taken was small sprout. Lead content was analyzed by using Absorption Automatic Spectrophotometer.  The results showed that mean content of lead in tea leaf at top hill was 3,4 µg/kg and mean content of lead at under hill was 5,7 µg/kg. The mean content of soil at top hill was 8,4 µg/kg and the average Pb content of soil at under hill was 7,5 µg/kg. After calculated by Mann-Whitney test found that there was difference Pb between concentration in the leaves on tea plants at top and under hills. There was no differences between lead concentration in soil at the top and under of hills. Test correlation with Spearman Rank found that there was correlation between Pb contents in the leaf of tea plants on the hill with soil at the hill. Study also showed that no correlation between lead content at tea leaf and soil at under of the hill.   Key words: Tea leaf (Camellia sinensis),  lead (Pb),  Malino tea plantation.